Lithium extraction from the mineral zinnwaldite: Part I: Effect of thermal treatment on properties and structure of zinnwaldite. (September 2017) - Schneider, A.; Schmidt, H.; Meven, M.; Brendler, E.; Kirchner, J.; Martin, G.; Bertau, M.; Voigt, W.
Highlights: The dehydroxylation mechanism of zinnwaldite was studied. 27 Al-NMR, F-NMR, Li-NMR, Mössbauer, IR spectroscopy were applied. The crystal structure of tempered zinnwaldite at 700 °C was resolved. β-spodumene, leucite, hematite and magnetite are the main decomposition products. Abstract: Lithium has become an energy critical element and thus the security of supply is of great importance. As a local German resource, attention was directed towards the mica-type mineral zinnwaldite. It represents a lithium-rich siderophyllite and corresponds to an intermediate polylithionite–siderophyllite solid solution with high contents of fluoride. Mineral samples from the deposit Zinnwald/Cínovec at the German/Czech border were analyzed and characterized by a variety of methods, particularly concerning its thermal behavior. Understanding the thermal behavior of the mica gives the opportunity to develop new and cost-efficient methods for lithium extraction. Investigations with different spectroscopic methods revealed the decomposition mechanisms. Starting at 300 °C, oxidation of Fe 2+ catalyzed the dehydroxylation of the mica by dehydrogenation. This is followed by a dehydroxylation similar to the mechanism of dioctahedral micas. At higher temperatures, the release of HF was detected. At about 800 °C the precipitation of hematite was observed. The complete decomposition of Zinnwaldite takes place at 900 °C, it is accompanied by the liberation of SiF4 and leads to the formation of several solid decomposition products. By means of single-crystal diffraction using X-rays and neutrons the structural changes could be identified after annealing at 700 °C. The results point to a transformation into a polylithionite-like structure, the end member of the solid solution series.